Case Study. (September 2015) - Maguire, Aoife; Castriciano, Giuseppa; Walker, Jan; Molloy, Karen; Quinn, Fiona; Osman, Nemer; Vandenberghe, Elisabeth; Jeffers, Michael; Gaffney, Eoin; Flavin, Richard
<x xml:space="preserve">Abstract</x> We describe an unexpected finding of diffuse large B-cell lymphoma associated with mature cystic teratoma of the ovary. A 68-yr-old woman with a complex left ovarian cystic mass on imaging underwent bilateral salpingo-oophorectomy, lymphadenectomy, appendicectomy, and omentectomy. Histopathologic examination revealed nodules of malignant non-Hodgkin lymphoma within the teratoma. A diagnosis of diffuse large B-cell lymphoma, germinal center cell subtype by Hans criteria was made after immunostaining and molecular studies. The patient was treated with R-CHOP chemotherapy and remains disease-free at 14-mo follow-up.